Climate change, urbanisation and transmission potential: Aedes aegypti mosquito projections forecast future arboviral disease hotspots in Brazil - Heath, Katherine; Muniz Alves, Lincoln; Bonsall, Michael B. (PLOS Neglected Tropical Diseases, 2025)
Author summary Aedes aegypti mosquitoes transmit viruses like dengue, Zika, and chikungunya, which are increasing in many parts of the world, including Brazil. Climate change and rapid urban growth are likely to increase the risk of mosquito-borne disease outbreaks in the future. In this study, we developed a model that combines mosquito biology with climate and urbanisation data to estimate how mosquito populations might change in Brazil under different future climate and development scenarios. Our model predicts that mosquito populations will increase significantly, especially in the South and Southeast of Brazil, where conditions are becoming more favourable for mosquito survival and reproduction. We also found that the risk of disease transmission is expected to rise as mosquito numbers grow faster than the human population. These findings suggest that both climate change and human development patterns are likely to increase the burden of mosquito-borne diseases. By showing where and when mosquito risks are likely to be greatest, our study can help public health authorities prepare and respond more effectively. It also highlights the importance of climate action to reduce future health risks.